Strengthening the Jombang AR Foundation as a New Foundation for Successor to the Old Foundation After the Foundation Law Regime - Mohammad Isrok; Radhityas Kharisma Nuryasinta (Universitas Negeri Semarang, 2023)
After the issuance of the Foundation Law, every Foundation that existed before the Foundation Law was required to adjust its Articles of Association with the provisions of the Foundation Law. If not, there will be legal implications for the Foundation, or in other words, the Foundation is legally weak which will also have an impact on the assets/wealth of the Foundation. Moving on from the results of observations, the service team found problems with the asset status/wealth of the Foundation caused by the less than optimal management of assets which must refer to the Waqf Law. Such problems place the position of the